Optimisation And Validation Of A New Microextraction Method Employing Surfactant For The Determination Of Selected Polycyclic Aromatic Hydrocarbons (PAHs) In Sugarcane Samples - Shater, Siti Farahiyah Ahmad (2016)
In the present study, a microextraction method termed ultrasound-assisted surfactant enhanced emulsification microextraction (UASEME) has been developed for the determination of phenanthrene (PHE) and fluoranthene (FLU) in sugarcane samples. Optimised extractions were obtained using the following conditions: extraction solvent, toluene; volume of extraction solvent, 30 μL; surfactant, Tween 20; volume of surfactant, 15 μL; extraction time; 2 min and with no salt addition. Under the optimized conditions, the method demonstrated good linearity (r2 ≥ 0.9932) over a concentration range of 1 to 1000 μg L- 1.